2012
DOI: 10.5402/2012/103892
|View full text |Cite
|
Sign up to set email alerts
|

Highlights in Seagrasses’ Phylogeny, Physiology, and Metabolism: What Makes Them Special?

Abstract: The marine seagrasses form an ecological and therefore paraphyletic group of marine hydrophilus angiosperms which evolved three to four times from land plants towards an aquatic and marine existence. Their taxonomy is not yet solved on the species level and below due to their reduced morphology. So far also molecular data did not completely solve the phylogenetic relationships. Thus, this group challenges a new definition for what a species is. Also their physiology is not well understood due to difficult expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 97 publications
0
62
0
2
Order By: Relevance
“…However, the phenolic secondary chemistry in the seagrasses appears not to have been fundamentally modified by this adaptation, as shown by the frequent occurrence of caffeic derivatives (Achamlale et al 2009, Nuissier et al 2010, Papenbrock 2012. Compared with terrestrial plants, using dead biomass of seagrass as a source of phytochemicals offers some particular advantages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the phenolic secondary chemistry in the seagrasses appears not to have been fundamentally modified by this adaptation, as shown by the frequent occurrence of caffeic derivatives (Achamlale et al 2009, Nuissier et al 2010, Papenbrock 2012. Compared with terrestrial plants, using dead biomass of seagrass as a source of phytochemicals offers some particular advantages.…”
Section: Discussionmentioning
confidence: 99%
“…An overview of seagrass metabolism, shows that the basic pool of secondary metabolites is similar to their terrestrial relatives from which they have evolved 3 . The biosynthesis of most secondary metabolites begins with a relatively small group of compounds, which are modified into an unlimited number of compounds through various synthesis pathways.…”
Section: Biogenesis Of Natural Productsmentioning
confidence: 99%
“…Z. noltii is rich in phenolic compounds and flavonoids such as, chlorogenic acid, caffeic acid, rosmarinic acid zosteric acid, apigenin, diosmetin, luteolin and luteolin-7-O-glucoside (Lamaison et al, 1990;Zeljan and Misko, 2000;Achamlale et al, 2009;Newberry et al, 2011;Sato et al, 2011). Additionally, crude extracts of seagrasses are shown to exert antibacterial, antifungal, antiviral, antioxidant, anti-inflammatory, antidiabetic and anti-cancer activities (Papenbrock, 2012). Moreover, we have shown that total extract of another seagrass, Posidonia oceanica has antioxidant, antidiabetic and vasoprotective effects (Gokce and Haznedaroglu, 2008).…”
Section: Introductionmentioning
confidence: 99%